1927 Haw. Sess. Laws 209-17, §§ 9, 12, 17 - (:unkn) unknown (My University, 1927)
AN ACT Regulating the Sale, Transfer and Possession of Certain Firearms and Ammunitions, and Amending Sections 2136, 2137, 2138, 2139, 2140, 2141, 2142, 2143, 2146 and 2147 of the Revised Laws of Hawaii 1925 (the "Small Arms Act"), § 9, § 12, § 17: Prohibited the transfer, sale, gift, loan, or otherwise of a pistol or revolver without a permit. Also prohibited the transfer of a pistol or revolver unless there is no reasonable cause that the transferee has not committed or is attempting to commit a crime of violence. Prohibited the transferee from furnishing false information or false evidence of their identity. Violators punished by fine of not more than one thousand dollars or imprisonment of not more than one year, or both.
Keywords: TRANSFER